(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
By the end of the 19th century, the world witnessed a sweeping technological revolution in information and communication technologies and scientific research, which made it necessary to open new horizons for improving and developing education and raising its quality. Algeria has been among the countries facing the problem of globalization, which brought with it many changes that hastened the reform of its educational system. The state has sought to spread the culture of technology and use its tools in the education sector, given its importance and in recognition of globalization’s strategies and possession of its means and tools. Thus, Algeria adopted the technology of e‑learning, aiming to eliminate the drawbacks of the traditional education model and to overcome the challenges and difficulties posed by that mode of education in an electronic environment, and to adopt a pattern of education that keeps pace with developments in other countries.